Short Communication: The mitochondrial cytochrome c oxidase subunit I (COI) for identification of batoids collected from landed sites in Medan, Indonesia - MUFTI SUDIBYO; khairiza lubis; ACHMAD FARAJALLAH; NISFA HANIM (Society for Indonesian Biodiversity, 2020)
Abstract. Lubis K, Sudibyo M, Farajallah A, Hanim N. 2020. Short Communication: The mitochondrial cytochrome c oxidase subunit I (COI) for identification of batoids collected from landing sites in Medan, Indonesia. Biodiversitas 21: 5414-5421.  Batoids are member of Elsamoranch subclass which consist of many species. Most of batoids species are overexploited, especially in Medan Indonesia. Up to presents, the information about diversity of rays on the east coast of North Sumatra, Indonesia was very limited. Therefore, this research aimed to investigate the diversity of rays on the east coast of North Sumatra. We examined the morphological trait of 82 individuals of batoid from three landing sites on the east coast of North Sumatra, namely: Tanjung Balai, Belawan, and Percut, then identify its species based on determination key. After that, we collected pectoral muscle tissue from an individual in each species which successfully identified to extract its genomic DNA. Molecular based identification was carried out by using DNA fragment form COI gene. The successfully amplificated COI gene DNA fragment then was sequenced and analyzed. Based on morphological trait, we successfully identifying nine species of batoid, which is Maculabatis gerrardi, Gymnura poecilura, Dasyatis zugei, Brevitrygon heterura, Neotrygon kuhlii, Hemitrygon bennettii, Rhinobatos jimbaranensis, Rhinoptera javanica, and Taeniura lymma. The result of identification based on COI gene DNA fragment was in congruent with morphological-based identification based on data BLAST-N and genetic distance value within same species. The nucleotide diversity within same species ranged from 0-15 nucleotide variants.